2 Kings 5 A Chiastic Quintet - Zucker, David J. 1942- (2023)
2 Kings 5 recounts the healing of the Aramean general Naaman through his encounter with Elisha the prophet of YHWH, and what then ensues with Elisha's attendant Gehazi. As structured the chapter reflects five sets of chiasms. This article breaks down those chiasms as it seeks to examine the story's focus in scripture.